Pelanggaran Prinsip Kesantunan Pada Tindak Tutur Ilokusi Karakter Tsundere Mikoshiba Dalam Anime Gekkan Shoujo Nozaki-Kun: The Violation of the Principle of Politeness in the Illocutionary Speech Acts of the Tsundere Character Mikoshiba in the Anime Gekkan Shoujo Nozaki-Kun - Dewi Salsabilla; Ruri Fadhillah Hakim; Muhammad Ali Hamdi (Undiksha Press, 2025)
Forms of speech that violate the principles of civility can be found in everyday life and in literary works, one of which is anime which is a typical Japanese animated cartoon. This research aimed to find out the speech that violates the principles of civility in illocutionary speech spoken by Mikoshiba, a tsundere character. This research used descriptive qualitative method with data collection technique in the form of listening technique by using advanced technique in the form of note-taking technique, and the analysis technique is contextual analysis method. Violation of the principle of politeness of illocutionary speech spoken by Mikoshiba, a tsundere character, was found as much as 23 data, dominated by the maxim of modesty, but no illocutionary speech was found that violated the maxim of sympathy. There are 16 meanings in Mikoshiba's illocutionary speech that violate the principle of courtesy, namely the meaning of prohibiting, refusing, inviting, ordering, complaining, ordering, regretting, insulting, underestimating, stating, promising, boasting, praising, denying, suggesting, and accepting.